Polysaccharide-Based Hydrogels for Microencapsulation of Stem Cells in Regenerative Medicine - Lee, Si-Yuen; Ma, Jingyi; Khoo, Tze Sean; Abdullah, Norfadhilatuladha; Nik Md Noordin Kahar, Nik Nur Farisha; Abdul Hamid, Zuratul Ain; Mustapha, Muzaimi (Frontiers in Bioengineering and Biotechnology, 2021)
Stem cell-based therapy appears as a promising strategy to induce regeneration of damaged and diseased tissues. However, low survival, poor engraftment and a lack of site-specificity are major drawbacks. Polysaccharide hydrogels can address these issues and offer several advantages as cell delivery vehicles. They have become very popular due to their unique properties such as high-water content, biocompatibility, biodegradability and flexibility. Polysaccharide polymers can be physically or chemically crosslinked to construct biomimetic hydrogels. Their resemblance to living tissues mimics the native three-dimensional extracellular matrix and supports stem cell survival, proliferation and differentiation. Given the intricate nature of communication between hydrogels and stem cells, understanding their interaction is crucial. Cells are incorporated with polysaccharide hydrogels using various microencapsulation techniques, allowing generation of more relevant models and further enhancement of stem cell therapies. This paper provides a comprehensive review of human stem cells and polysaccharide hydrogels most used in regenerative medicine. The recent and advanced stem cell microencapsulation techniques, which include extrusion, emulsion, lithography, microfluidics, superhydrophobic surfaces and bioprinting, are described. This review also discusses current progress in clinical translation of stem-cell encapsulated polysaccharide hydrogels for cell delivery and disease modeling (drug testing and discovery) with focuses on musculoskeletal, nervous, cardiac and cancerous tissues.